Enlivening the mosque as a public space for social sustainability of traditional Malay settlements - Jaffar, Najiha; Harun, Nor Zalina; Abdullah, Alias (Malaysian Institute Of Planners, 2020)
Public spaces are vital elements of settlement fabrics that animate communities together in one place. Nevertheless, most public places are used for recreational purposes only without building on communal activities, especially in religious aspects. Therefore, to achieve robust social sustainability, this study aims to identify the key indicators for ensuring social sustainability of traditional settlements’ public spaces. This study explores the typologies of public spaces found in traditional settlements that fill the needs of the local community. A mixed methodology was used to map and observe the public spaces and the communal activities held in two traditional Malay settlements in Kuala Terengganu. The bulk of the data were randomly collected from 400 residents by using a questionnaire survey to identify the most relevant factors that influence social sustainability. The results show that mosques have been listed as the highest preference of public space in the two sampled settlements. The study outlines three key qualities that lead the community to choose the mosque as the most important public space: 1) convenient access, 2) comfortable and clean, and 3) social aspects. This paper concludes on how these findings contribute to the improvement of quality of life, social interaction and social cohesion to achieve the Sustainable Development Goals (SDGs) globally.